2014
DOI: 10.5539/gjhs.v6n5p105
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Concern and its Correlates among Male and Female Undergraduate Students at Assuit University in Egypt

Abstract: Introduction:This cross-sectional study examined variables associated with body image concern (BIC) and whether these associations differed between female and male students in Egypt. During the period 2009-2010, 3271 undergraduate students (1663 females, 1504 males) at Assuit University in Egypt completed a self-administered questionnaire that assessed BIC and other socio-demographic and health related variables.Methods:Based on Cooper et al.’s Body Shape Questionnaire the authors categorized BIC into ‘no BIC’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 57 publications
5
29
1
Order By: Relevance
“…Studies simultaneously evaluating physical form and body image were not found. Women, as compared to men, generally perceive themselves as being a little heavier, and wish to look thinner, confirming previous reports in university population (32), in adolescents (33), and in adults (34). We found 13% to 48% consistency among what participants thought about their body image and what they wish, and think, and believed how others see them (Table II).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies simultaneously evaluating physical form and body image were not found. Women, as compared to men, generally perceive themselves as being a little heavier, and wish to look thinner, confirming previous reports in university population (32), in adolescents (33), and in adults (34). We found 13% to 48% consistency among what participants thought about their body image and what they wish, and think, and believed how others see them (Table II).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, both men and women showed high dissatisfaction with their own body shape (75%); the higher the overweight and obesity, the higher the dissatisfaction with their body shape. El Ansari et al (32) reported 15% higher unconformity on body image in young university women vs men, and in both cases that unconformity was directly proportional to BMI; furthermore, it was associated with depression and poor life style. We found that women show 30% more disagreement with their bodies as compared to men, and they wish to be thinner (79%).…”
Section: Discussionmentioning
confidence: 98%
“…This is contrary to results realized by studies conducted in Western countries, which have tended to suggest the prevalence of body image dissatisfaction, especially among young adults, including among university students (see e.g., Ansari et al, 2014;Ferrari et al, 2013;Goswmi, Sachdeva and Sachdeva, 2012). It should be noted that the existence of low levels of body image dissatisfaction adduced by this study is backed up by the absence of the symptoms of negative body image consequences -such as attempted suicide, suicide thoughts, withdrawal from friends/peers/colleagues, and eating disorders -among the bulk of those who were interviewed for the study.…”
Section: Discussioncontrasting
confidence: 67%
“…The scope of the current research is in line with other general student health and wellbeing surveys undertaken in a number of countries [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 88%